The Impact of Sustainability on Co-Creation of Digital Public Services - Noella Edelmann; Shefali Virkar (Administrative Sciences, 2023)
Co-creation focuses on engagement with citizens and other stakeholders with public administrations to develop innovative processes or public services. The integration of resources and knowledge mediated by technology can lead to the emergence of novel outcomes (such as products, services, processes, and social practices), but it is necessary to understand the mechanisms that lead to sustainable co-created innovation and outcomes. The aim of this research article is to contribute a more nuanced understanding of the impact of sustainability on co-creation of digital public services. To study co-creation and sustainability in the context of the public administrations in depth, a qualitative research approach was used. The data were collected through moderated discussions conducted during a workshop held with 20 experts and practitioners in the field of public sector digital transformation, during which participants shared their views and experiences in a free-flowing conversation. A systematic two-cycle analysis approach based on Grounded Theory was used to code and analyse the data collected. Results from this study focus on developing a common understanding of sustainability within the context of co-created digital public services, an exploration of how sustainability in public administrations may be supported by co-creation and a critical examination of the elements that contribute to the sustainability of digital public services—all drawing on existing examples of co-creation initiatives from within the public sector.